Kontruksi ldentitas Melalui Stories Highlight Instagram Kalangan Kelas Menengah - Rama Kertamukti; Heru Nugroho; Sugeng Bayu Wahyono (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2019)
Instagram as a cyber commodity wants to unite and become an entity in the community lifestyle. Inter-human communication on Instagram can occur at any time during online connection, almost every user activity can be captured and published on Instagram in seconds. The production and consumption of messages happening on Instagram is done on Instagram Stories as a production of middle class status messages. This study aims to find identity construction through stories highlight Instagram. This study uses a qualitative method, examining how identity construction through Instagram Stories owned by Instagram by the middle class with informant accounts @putrilellyana, @rosakusumaazhar, @herni_maryuliani, @ taufik.mbantul, @fajarmantoo. This research was conducted using virtual ethnography and independent interviews to explore data in order to get answers to research problems. Middle-class informants show that Instagram as a visual media is able to present certain symbols as a tool to produce meaning from an identity to be conveyed. The self presented by informants on Instagram Stories reflects leisure informants in carrying out activities freely in life such as hobbies, recreation, increasing knowledge about art and culture and also filling in actual activities for leisure time. Continuous research on codes, values, and beliefs about culture as a whole on Instagram needs to be explored to show the results of technology that is acculturated with economic, social and cultural factors.